Respuesta :

Here, we know, 3³ = 27
So, missing exponent was 3

Hope this helps!
Answer: The missing exponent is "3".
____________________________________________________
27 = 3^3 ; that is 27 = 3³ ; since 3 × 3 × 3.
____________________________________________________
Alternatively, the missing exponent is: "⅓" ;
____________________________________________________
27^(
⅓) = 3 ;

Since: 27^(
⅓) = ∛27 = 3 .
_______________________________________________
     It is a matter of which side of the "equation" you want to place your "missing exponent" in the "equation" given:  27 = 3 .
____________________________________________________